2018
DOI: 10.1080/14767058.2018.1424131
|View full text |Cite
|
Sign up to set email alerts
|

An appropriate way to predict fetal gender at first trimester: anogenital distance

Abstract: Gender can be detected with great accuracy in gestations between 11 to 13 weeks and 6 days by using AGD. CRL and gestational week (GW) were determined as nonsignificant predictors of fetal gender by AGD measurement. In order to obtain more accurate results with AGD, consideration of further studies with larger series in different races is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Recent studies reported significantly different AGD values between races, recommending that population-specific normative values are needed for accurate clinical assessment. 9,10 These factors support the rationale for conducting this study.…”
mentioning
confidence: 56%
See 2 more Smart Citations
“…Recent studies reported significantly different AGD values between races, recommending that population-specific normative values are needed for accurate clinical assessment. 9,10 These factors support the rationale for conducting this study.…”
mentioning
confidence: 56%
“…5,6 Anogenital distance (AGD) is a recently introduced sonographic marker of fetal gender. [7][8][9][10][11] It is based on measuring the distance between the anus and the base of the genital tubercle in the perineal region. 12 Anogenital distance is sexually dimorphic since its length is dependent on hormonal levels.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As in rodents, human males have a longer AGD than females at birth/during childhood and adulthood [10][11][12][13][14] (Figure 1). This sex difference first emerges at 11-13 weeks' gestation and becomes maximally different (1.7-to 2-fold) by 17-20 weeks' gestation, whether measured directly in abortuses [15,16] or in utero by ultrasound [17][18][19][20][21]. Thus, if the male-female difference in AGD is determined in humans in a MPW, as it is in rodents, this clearly locates the MPW in the 1st trimester, probably within the period 8-14 weeks' gestation [7,10] (Figure 1).…”
Section: Introductionmentioning
confidence: 98%
“…Although there is a lack of statistical evidence on this male-female difference before and during adolescence, the difference has been shown to be maintained throughout adulthood. The difference has been observed in firsttrimester fetuses by transabdominal ultrasound, and a shorter AGD in male fetuses indicates diseases associated with testicular dysplasia syndrome (3)(4)(5). According to rodent models and human data, the AGD of an individual changes as their body grows (6).…”
Section: Introductionmentioning
confidence: 99%